Practical patient safety - Reynard, John (Oxford University Press, 2009)
Following recent high profile cases of surgical error in the UK and USA, patient safety has become a key issue in healthcare, now placed at heart of junior doctor's training. Errors made by doctors are very similar to those made in other high risk organisations, such as aviation, nuclear and petrochemical industries. Practical Patient Safety aims to demonstrate how core principles of safety from these industries can be applied in surgical and medical practice, in particular through training for health care professionals and healthcare managers. Whilst theoretical aspects of risk management form.